Model Bisnis Langganan dalam Platform Dakwah Digital: Perspektif Fikih dan Manajemen Syariah - Asep Koswara; Ela Sartika; Dedi Kuswandi (Program Studi Manajemen Dakwah Fakultas Ushuluddin Dan Dakwah Uin Raden Mas Said Surakarta, 2026)
This study examines the compliance of subscription-based business models in digital da’wah platforms with Islamic jurisprudence principles within the Sharia economics framework, with particular reference to platforms such as Muslim Pro and Tarteel AI. The rise of digital da’wah has led to paid subscription schemes that raise debates concerning contract clarity and potential gharar elements. This research uses a qualitative approach through literature review and conceptual analysis of the ijarah al-manfa‘ah contract in the digital context. The findings indicate that subscription models can be classified as ijarah al-manfa‘ah if the contract object involves clearly defined service access, specified duration, and transparent user benefits. With proper contract structuring, the model is not only Sharia-compliant but also supports the sustainability and professionalism of digital da’wah management. The study contributes theoretically to Islamic digital business literature and practically to guiding ethical business model design for digital da’wah platforms.